Manuscript Digitization Efforts as a Means of Cultural Heritage Preservation in Serang Regency: A Case Study of the Region VIII Cultural Heritage Preservation Office, Banten - Muhammad Fikri Azka Haikal; Tubagus Umar Syarif Hadi Wibowo; Agus Rustamana (UIN Imam Bonjol Padang, 2026)
This research aims to describe the history and role of the Cultural Preservation Center Region VIII in preserving cultural heritage in Serang Regency, analyze the manuscript digitalization process as a cultural heritage preservation effort, and identify the impact of manuscript digitalization for the community, pupils, and students in Serang Regency. This research uses a qualitative method with a case study approach. Data collection was conducted through observation, in-depth interviews, and documentation studies involving eight informants consisting of three staff members of the Cultural Preservation Center Region VIII/Cultural Experts, the Acting Head of the Library and Archives Office of Serang Regency, two practitioners and academics, and one member of the Cilegon City Cultural Council. Data validity was ensured through source triangulation, including key informant interviews, field observations, and document studies. The research results show that the digitalization of manuscripts in Serang Regency is a crucial step in safeguarding cultural heritage, yet it faces challenges such as the damaged and fragile physical condition of the manuscripts, limited digitalization equipment, and a lack of competent human resources in the field of manuscript conservation. This research concludes that manuscript digitalization is able to minimize the risk of physical damage while ensuring the accessibility of cultural information for future generations; therefore, strengthening human resource capacity and synergy between institutions is required to support the sustainability of regional cultural heritage preservation